PENGEMBANGAN MEDIA BOARD GAME DALAM MENGENAL EMOSI ANAK DI KELOMPOK A TK NEGERI PEMBINA SAMPOROA - Ramadhani, Nurul; Agusniatih , Andi; Nirmala, Besse; Imamah, Zakiyyatul; Agusniatih, Andi (Bunayya, 2026)
This study addresses children’s limited ability to identify emotions and the lack of interactive media in schools. It aims to develop a feasible and effective board game for Group A students at Pembina Samporoa Public Kindergarten. Using the ADDIE R&D model, 12 students participated as research subjects. Validation results indicated high feasibility, with a score of 97.5% from media experts and 92.5% from content and language experts. Field testing revealed an improvement in the children’s abilities, with an average pretest score of 5.25 and a posttest score of 7.83. An N-Gain score of 0.45 confirms that this improvement falls within the moderate category. The study’s novelty lies in integrating contextual narratives that transform abstract emotional concepts into concrete experiences. It is concluded that the board game is feasible and effective as a tool for stimulating emotional development. This medium provides an interactive alternative to optimize the affective aspects of early childhood.